Natural levels of colour polymorphism reduce performance of visual predators searching for camouflaged prey. (20th May 2014) - Karpestam, Einat; Merilaita, Sami; Forsman, Anders
<x xml:space="preserve">Abstract</x> Polymorphism, the coexistence of two or more variants within a population, has served as a classic model system to address questions about the evolution and maintenance of intraspecific variation. It has been hypothesized that a natural level of colour polymorphism may impair the search efficiency of visually orientated predators. To test this polymorphism protects hypothesis, we asked human participants to search for images of natural black, striped or grey Tetrix subulata grasshopper colour morphs presented against photographs of their natural habitat on computer screens. Fewer grasshoppers were detected when morphs were presented in mixed than in uniform sequences. All three morphs benefited to comparable degrees, in terms of reduced detection, from being presented in polymorphic sequences. Our findings demonstrate that natural levels of polymorphic variation can impede the efficiency of visually orientated predators and increase survival of prey. This protective effect supports the limited attention hypothesis, explains why predators develop 'search images', may account for the spread and establishment of novel colour variants, and contributes to maintenance of polymorphisms. © 2014 The Authors. Biological Journal of the Linnean Society published by John Wiley & Sons Ltd on behalf of The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 546–555.